Kanoniczne przeszkody małżeńskie – zarys problematyki - Góralski, Wojciech (Ius Matrimoniale, 2016)
One of fundamental human rights, based on natural law and guaranteed by can. 219 of the current CIC, is the right to choose a state in life freely. However, at the same time the church legislator states that all persons who are not prohibited by law can contract marriage (can. 1058). The restriction on the right to contract marriage may come from God’s law (natural and positive), as well as from the decision of the church legislator. One of factors limiting ius connubii are impediments to marriage, namely circumstances related to particular persons which make them unfit to contract valid marriage. Following an analysis of the definition of an impediment to marriage, the author presents a historical outline of the development of impediments, quotes the catalogue of impediments that are currently applicable, presents the legal character and function of impediments and describes their types (according to various criteria). Finally, the author presents issues regulated in chapters II and III of De matrimonio.